The Effectiveness of Moodle-Based Learning Management Systems in Enhancing Students’ Academic Readiness for Computer-Based Tests (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
The rapid advancement of digital technology in higher education has transformed learning and assessment systems, particularly through the adoption of Learning Management Systems (LMS) and Computer-Based Tests (CBT). However, many university students still face challenges in adapting to digital examination environments due to limited technical experience and digital literacy. This Community Service Activity (PKM) aims to enhance students’ academic readiness and digital competence through the implementation of a Moodle-based LMS at Universitas Murni Teguh. The activity was conducted in the form of an interactive workshop, including system introduction, simulation of CBT, guided practice, and discussion sessions involving university students and lecturers. The results showed a significant improvement in students’ understanding of LMS features, confidence in using CBT systems, and ability to manage digital-based examinations effectively. Active participation and engagement during the sessions reflected high enthusiasm and adaptability toward digital learning transformation. This activity demonstrates that the implementation of LMS Moodle is effective in improving academic preparedness and digital literacy among students, and can serve as a sustainable model for strengthening technology-based learning in higher education institutions.